Threats posed by CBRN terrorism and the role of the SEDM-CBSC working group in the prevention and response - Bokan, S.; Chalaris, Michail; Stavrakakis, P.; Sarafis, Pavlos (My University, 2010)
The South-Eastern Europe Defence Ministers on December 2001 endorsed the establishment of a Working Group on 'Defence/Military Support to Weapon Mass Destruction (WMD) Counter-Proliferation, Border Security, and Counter-Terrorism' (CBSC) as a result of a decade of changes in South-Eastern Europe (SEE), the terrorist events of Sep. 11 in the USA, and the related NATO process of adaptation to the new s.curity environment, reinforced awareness within the international community of the need for preventing and countering WMD proliferation, s.rengthening border s.curity, and taking concrete s.eps to combat and deter international terrorism in all its forms. The changing international s.curity environment and the emergence of asymmetric and non-conventional threats in SEE created the need for a regional approach to develop common plans and s.rategies through enhancing coordination among the different s.curity agencies. This initiative fully s.pports current international efforts to promote CBSC in SEE, taking also into account other initiatives in the region s.onsored by the UN, EU, NATO and OSCE. Since the establishment of the CBSC WG, the WG members participated in a lot of activities including a number of relevant s.minars and conferences organised by SEDM nations, and they also push forward measures to improve transparency and visibility of the WG, by opening up to cooperation with other organisations and processes. The main threat today undoubtedly is CBRN terrorism. International terrorism includes s.reading of WMD technology and expertise. WMD information is widely accessible and highly-trained engineers and physicists employed s.reading throughout the world. Organised and general international crimes include the s.uggling of WMD and related material, dual-use goods and transfers of NBC technologies, equipment, agents and knowledge.
Keywords: Global proliferation threat; Practical levels of non-proliferation policy; Scientific and technical realities; Threats posed by cbrn terrorism